Warrior Race : A Journey Through the Land of the Tribal Pathans - Imran Khan (London Chatto & Windus, 1993)
Imran Khan's family are Pathans from the fiercely independent tribal areas of the north-west frontier province of Pakistan. In this book he makes a journey through wild and hostile terrain, finding a proud and warlike people who received him with great generosity and quiet courtesy.
Include Color Illustrations
Keywords: Travel -- Pushtuns--Social Conditions